Da competência técnica à competência organizacional: uma abordagem teórica sobre as funções do instrumentista de manutenção - Vieira, Elisabeth Mendes (2009)
In environments where technological innovation is part of the strategy, the resources invested and the skills developed by the organization become sources of competitive advantage. The labor market requires increasingly skills and specialization of labor, especially in the area of industrial maintenance, turning the maintenance management a strategic segment for organizations. In Brazil, the establishment of professional certification for the maintenance is ABRAMAN - Brazilian Association of Maintenance, which has as parameter the profile presented by the Standard ABNT - Brazilian Association of Standards and Techniques - NBR 15150/2004. The problem investigated was: What are the competences - knowledge, skills and attitudes that should complement the technical profile of the professional instrumentalist in industrial maintenance, taking into consideration the demands of the new management model of production. This study had as general objective to identify organizational, essential and technical competences for maintenance instrumentalist, pondering the professional profile required for his participation in the strategic management of production. A theoretical scenario was build which would identify the skills required in changing environments, and also an interpretative scenario was elaborated, containing the competences required by the Industrial Maintenance Instrumentalist certified by ABNT NBR 15150/2004. The research had as its starting point the literature and scientific works on Production Engineering and Maintenance, and Manufacturing Process Management, which present studies and discussions focusing on these concerns and might contribute to a preliminary analysis of the competences required for the proper performance of this professional in strategic management of production. The results showed that the concern in the process of certification of professional instrumentalist regulated by the NBR 15150/2004 and implemented by ABRAMAN is focused on knowledge and technical skills, not including organizational competences, which are essential, thus characterizing a model not based on competences. It was also possible to identify a set of skills, knowledge and attitudes that will enrich the list of competences required by the Industrial Maintenance Instrumentalist I and II - regulation ABNT NBR 15150/2004, inserting it into a process of development and management skills that complement the technical knowledge, therefore requiring initiative, independence, dedication, agility of thought, creativity, logical reasoning, versatility, determination, strategic vision, interest, availability, persistence and commitment.